Realization for low cost and energy efficient ceiling fans in the developing countries. (September 2017) - Tauqeer, Tauseef; Ansari, Muhammad Afnan; Hasan, Ammar
Abstract: This article focuses on power consumption mitigation of ceiling fan through induction motor design optimization. Efficiency of the fan is vastly dependent on the motor design i.e. the materials and techniques used to build the motor. The fan industry in developing countries like Pakistan are using inefficient design techniques in addition to the low grade materials to manufacture the motors. Consequently, none of the locally available fans of Pakistan market are able to meet international standards. High electricity cost, increased power consumption and the incapability to meet international standards are the prime motivations to improve the existing design practices in the fan industry of Pakistan. Detailed analysis and experiments are performed with nine ceiling fans manufactured and tested at a fan industry located in Gujrat, Pakistan. Design optimization predicted 35% improvement in the energy profile, which is latter verified by the experimentation. Seven out of the nine Designed Ceiling Fans (DCFs ) met the characterization of Pakistan Standard 1 (PS1) and six met the Bureau of Energy Efficiency (BEE) star ratings specifications. A comprehensive comparison is carried out between commercially available ceiling fans (CCFs ) and DCFs with respect to energy consumption, standards, annual customer saving, impact on national grid and performance. In addition, a fan characterization platform is developed for better quality control and logging of the electrical parameters during fan manufacturing. In order to achieve static balancing, an automatic blade sorter is designed to bundle the blades with same weight before shipment.